Production and Characterization of B4C Content-Dependent Aluminum Matrix Composites Fabricated via Hot Pressing - Bayrak, Yahya; Kisasoz, Alptekin; Sezer, Rasit (SPRINGER, 2025)
In this study, Al/B4C composites were fabricated by a vacuum hot pressing process with various B4C contents. Microstructure, corrosion behavior, physical and tribological properties of the produced samples were investigated. The samples were characterized by x-ray diffraction analyses, microstructural investigations, and Archimedes tests. The microstructure properties were studied with light microscopy, scanning electron microscopy and energy dispersive spectrometry analyses. Also, dry sliding wear tests, corrosion tests, hardness and electrical conductivity measurements were performed to reveal the effect of B4C particles on the properties of the commercial pure aluminum matrix. Microstructural analysis revealed that composite production was achieved up to 15 wt.% B4C content without forming intermetallic phases. The wear resistance of the aluminum was improved by increasing B4C content. Also, the corrosion rate of the aluminum was reduced from 0.1698 to 0.0587 mm/year by adding 15 wt.% B4C. On the other hand, the electrical conductivity of the aluminum was decreased with the increasing reinforcement content and porosity. Results showed that Al/B4C composite production was achieved, and the corrosion and tribological properties of the aluminum were improved by the existence of the B4C particles.
Keywords: ceramic particles; characterization; composite; corrosion; powder metallurgy; wear; MECHANICAL-PROPERTIES; WEAR BEHAVIOR; CORROSION CHARACTERISTICS; PARTICLE-SIZE; MICROSTRUCTURE; ALLOY; AL-B4C; REINFORCEMENT; INFILTRATION; MORPHOLOGY; Materials Science